(untitled) (Research, Society and Development, 2020)
The knowledge of the characteristics of the hydrographic basins of a region is characterized as information to aid decision making related to the various economic and social activities, such as water supply, power generation and availability of water for irrigation. In this sense, the present study aimed to identify in the municipality of Cristalina, Goiás, the number of central pivots present in the hydrographic micro basins, making notes on the rules for granting abstraction flows through estimates. For this purpose, the computational application ArcMap 10.5 and satellite images Sentinel-2 and Shuttle Radar Topography Mission were used to identify the number of central pivots and microbasins in that municipality in Goiás. Data provided by the State Secretariat for the Environment, Water Resources, Infrastructure, Cities and Metropolitan Affairs and the Hydroweb System of the National Water Resources Information System were also used. One hundred forty-seven microbasins were identified in the municipality of Cristalina, Goiás, which were grouped into classes, according to their areas. Between 2010 and 2017, 204 central pivots were installed, which corresponded to an increase of 77.56% in the municipality’s irrigated area. The average intake flow estimated by the central pivot was 72.73 m3 h-1, resulting in an increase in the demand for water abstraction of 14,836.92 m3 h-1 in the evaluated period. The data obtained will contribute to the application of the consumptive flow granting rules, if the Q95 values are established in their outlets, allowing a more adequate number of equipment installed in the microbasins.